2021
DOI: 10.1021/acs.jpcb.1c00719
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Excitation Energy Transfer from the Bacteriochlorophyll Soret Band to Carotenoids in Photosynthetic Complexes of Purple Bacteria

Abstract: The excitation energy transfer (EET) from the bacteriochlorophyll (BChl) Soret band to the second excited state(s) (S2) of carotenoids in pigment–protein complexes of purple bacteria was investigated. The efficiency of EET was determined, based on fluorescence excitation and absorption spectra of chromatophores, peripheral light-harvesting complexes (LH2), core complexes (LH1-RC), and pigments in solution. Carotenoid-containing and carotenoid-less samples were compared: LH1-RC and LH2 from Allochromatium minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…By analyzing the NTOs for these bands, it is shown that in all of these states, the DHN molecules play an important role in a charge transfer state (see Figure ), the same holds true for the transition from the 540 nm band of B6 . This phenomenon is already reported on plants and bacteria. However, it is also known that the energy transfer from the BChl Soret band to carotenoids has an extremely low efficiency; in fact, when the DHN molecule is deleted, the 770 nm band is lost (e.g., see the case of system B7 in Figure S12 of the SI).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…By analyzing the NTOs for these bands, it is shown that in all of these states, the DHN molecules play an important role in a charge transfer state (see Figure ), the same holds true for the transition from the 540 nm band of B6 . This phenomenon is already reported on plants and bacteria. However, it is also known that the energy transfer from the BChl Soret band to carotenoids has an extremely low efficiency; in fact, when the DHN molecule is deleted, the 770 nm band is lost (e.g., see the case of system B7 in Figure S12 of the SI).…”
Section: Resultssupporting
confidence: 64%
“…This phenomenon is already reported on plants and bacteria. 46−48 However, it is also known that the energy transfer from the BChl Soret band to carotenoids has an extremely low efficiency; 49 in fact, when the DHN molecule is deleted, the 770 nm band is lost (e.g., see the case of system B7 in Figure S12 of the SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to compare our results to the experimental results from refs , , we take another step in the calculation and convert the density shown in Figure to current, i.e., to the signal that can be detected in an experiment. The relation between density and currents is easily obtained by simply multiplying the density of a state by the rate of extraction from that state.…”
Section: Discussionmentioning
confidence: 99%
“…When this is done, it is found that the signal from the lycopene S2 state when excited from the BChls is ∼3% (Figure 2), close to the experimental results. 28,48 The authors of ref 28 argue that the low signal from the lycopenes is due to the blocking of exciton flow from BChls to the lycopenes, which maybe due to the weak coupling between the BChl and lycopene states. 48 However, this argument is inconsistent because if the current is blocked because of weak coupling, then it would have been blocked also when exciting in the opposite pathway, in contradiction to the experimental observations (which show substantial signal in the reverse pathway).…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation